EXAMINING THE CHALLENGES OF FORECASTING AS A TOOL FOR PROCUREMENT: THE CASE OF STANBIC BANK – GHANA. - OWUSU, JAMES YAW OSEI –; OKYERE, PHILIP OBENG –; BOADI, REBECCA AGYEIWAA; DOTSE, CALVIN FEMI (IJRDO - Journal of Business Management, 2016)
The project work was titled “examining the use of forecasting as a tool for procurement”Stanbic Height in Accra, the capital town of Ghana was chosen as a case of study.The research work was organised into five coherent chapters. Chapter one was basically the introductory; part of the research work. An extensive literature on the research work was piled up at chapter two. Both qualitative and quantitative techniques were used as methodology to collect data for the research work. Interesting findings such as benefits that accrues from forecasting as a tool for procurement were revealed. Helps in planning, inventory management and learning from the past are some benefits. Areas of procurement were forecasting plays a greater role at Stanbic Height were also revealed from the research, material control, logistics planning, budgeting for goods, services and works are some examples. The research was concluded with the statement that, all the objectives set for the research were achieved; therefore organisations and firms should put in more resources to always undertake forecasting as an exercise with the simple reason that it will help them to do useful prediction into the future. The research finally ended with good recommendations, amongst which it was recommended that, educational programs should also be annually organised for the team responsible for forecasting in every department at Stanbic bank, Ghana so that they will be abreast with current and innovative ways of handling the techniques and strategies involved in forecasting. Stanbic bank Ghana can reliable do this through the organization of seminars, workshops and conferences